1987
DOI: 10.1128/jvi.61.11.3570-3579.1987
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of differentiated rat hepatocytes with adenovirus and adenovirus DNA

Abstract: Primary cultures of hepatocytes isolated by collagenase perfusion of adult rats were transformed by infection with adenovirus type 5 or transfection with adenovirus DNA. Total virion DNA or recombinant plasmid DNA containing the adenovirus EIA and E1B genes transformed hepatocytes at comparable frequencies. No foci of replicating hepatocytes were detected after transfection with a plasmid containing the ElA gene alone. The frequency of transformation by the adenovirus EIA and E1B genes was dependent on the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…As the cultures age, no space remains between hepatocytes within the islands and paracellular junctions between adjoining cells can be observed by electron microscopy. 16,20 Primary rat hepatocytes in long-term DMSO culture have been used to study the molecular mechanisms of albumin expression, 17,21 altered growth control including induction of DNA synthesis and proliferation, 22 immortalization and transformation, [23][24][25] as well as programmed cell death. 26 More recently, we have demonstrated that hepatocytes in long-term DMSO culture function as an ideal model system for studying chronic iron loading of hepatocytes.…”
Section: Iron Loading Of Hepatocytes Resulted In Decreased E-cadherinmentioning
confidence: 99%
“…As the cultures age, no space remains between hepatocytes within the islands and paracellular junctions between adjoining cells can be observed by electron microscopy. 16,20 Primary rat hepatocytes in long-term DMSO culture have been used to study the molecular mechanisms of albumin expression, 17,21 altered growth control including induction of DNA synthesis and proliferation, 22 immortalization and transformation, [23][24][25] as well as programmed cell death. 26 More recently, we have demonstrated that hepatocytes in long-term DMSO culture function as an ideal model system for studying chronic iron loading of hepatocytes.…”
Section: Iron Loading Of Hepatocytes Resulted In Decreased E-cadherinmentioning
confidence: 99%
“…Immortalized hepatocytes are typically derived from healthy primary hepatocytes by using a defined immortalization strategy. Both fetal and adult hepatocytes from different species have already been successfully immortalized, whether or not using a combination of viral oncogenes and the human telomerase reverse transcriptase (hTERT) protein [7, 9, 19-25]. The purpose of this paper is to discuss the different current immortalization strategies and provide an overview of the actually available immortalized hepatic cell lines and their applications.…”
Section: Introductionmentioning
confidence: 99%
“…In culture, neither transformation nor immortalization of primary rodent hepatocytes by activated rus transfection has been successful in our laboratories or in those of others, even when combined with active cellular replication induced by specific growth stimuli, although the simian virus 40 DNA or adenovirus DNA has been reported to be capable of immortalizing rat hepatocytes (Woodworth et al, 1986;Woodworth and Isom, 1987;Paul et al, 1988). This suggests that activation of the rus oncogene may not be an effective initiating event in the in vitro hepatocyte transformation system.…”
Section: Discussionmentioning
confidence: 99%